The Influence of English as a Foreign Language Teachers’ Positive Mood and Hope on Their Academic Buoyancy: A Theoretical Review - Dong, Hui; Li, Wei; Ye, Di (Frontiers in Psychology, 2022)
Emotions are now considered critical elements of a successful education. In English as a Foreign Language (EFL) context, there are many challenges for teachers to deal with. Hence, it is necessary to take their emotions into consideration. Despite many studies in this area, researching teachers’ positive mood, hope, and academic buoyancy has been left less attended. Trying to introduce this line, the present study reviewed the definitions, related concepts, theories, and previous studies done on these three variables in detail. It also touched upon the origins of researching emotion in educational contexts describing different schools of psychology. Additionally, the study offered some practical implications for EFL teachers, students, policy-makers, teacher trainers, and researchers. Finally, it enumerated the existing gaps in this area and made a number of research suggestions for future research.